The impact of the strategic action plan to combat chronic non-communicable diseases on hospital admissions and deaths from cardiovascular diseases in Brazil. - Rafaella Alves da Silva; Luiza Gabriela de Araújo Fonseca; João Pedro de Santana Silva; Núbia Maria Freire Vieira Lima; Lucien Peroni Gualdi; Illia Nadinne Dantas Florentino Lima (PLoS ONE)
Chronic Non-Communicable Diseases (NCDs) are the main causes of death worldwide, responsible for millions of hospital admissions per year, especially cardiovascular diseases (CVD). Several strategies for controlling and coping with these diseases have been developed in several countries. The aim of the study was to evaluate the impact of the Strategic Action Plan to Combat NCDs (2011-2022) on hospital admissions, deaths and mortality rate in Brazil, classified by CVD. This is a descriptive study, with secondary data from the Hospital Information System of the Unified Health System (SIH/SUS). Hospital admissions, deaths and mortality rate due to CVD in the Brazilian population aged over 20 years were analyzed, according to region, sex and age group. Statistical analysis was performed using the GraphPad Prism program. Data normality was assessed using the Komogorov Smirnov test and the comparison between groups and year periods was performed using the two-way ANOVA test with Tukey's post hoc test. A value of p<0.05 was considered significant. In this study, in most analyses, a reduction in the hospitalization rates of the adult population was observed after the implementation of the plan, however, there was no improvement in relation to the number of deaths and mortality rate from CVD. This shows that there is still a long way to go to reduce the impact of these diseases in Brazil, and they reaffirm the need for and importance of maintaining the prevention of their risk factors, the social determinants of health and the reorganization of care in the face of to population aging. Such findings contribute with information that allow better control and monitoring of CVD and should be considered when implementing new strategies for prevention, care and control of risk factors.